I'm a Trustee, get me out of here (with indemnities and security). Issue 2 (25th January 2019) - Talbot Rice, Elspeth
Abstract: This article is a wake-up call for trustees: it looks at the Chief Justice's decision in the Supreme Court of Bermuda in Meritus v Butterfield, which exposes as a myth the notion that an outgoing trustee is entitled to insist on contractual indemnities or to retain trust assets as security against potential trust liabilities.